2022
DOI: 10.2196/35788
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Establish Race or Ethnicity of Twitter Users: Scoping Review

Abstract: Background A growing amount of health research uses social media data. Those critical of social media research often cite that it may be unrepresentative of the population; however, the suitability of social media data in digital epidemiology is more nuanced. Identifying the demographics of social media users can help establish representativeness. Objective This study aims to identify the different approaches or combination of approaches to extract race… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 170 publications
(212 reference statements)
0
10
0
Order By: Relevance
“…Namely, the likelihood of segregation in networks, an effect known as filter bubble [32,34], and the ranking signals that govern how message contents become available to users in a network [3,21,29]. Other issues have been identified derived from online recruitment, especifically participant retention [28], age bias [17] and racial and economical bias [19,31,50]. Some studies have shown that community-based methods, including personal references, local advertisements and pamphlets, indeed recruit more racially diverse samples than other methods [41], and may ensure better chances of participant retention [2,7,44,46,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the likelihood of segregation in networks, an effect known as filter bubble [32,34], and the ranking signals that govern how message contents become available to users in a network [3,21,29]. Other issues have been identified derived from online recruitment, especifically participant retention [28], age bias [17] and racial and economical bias [19,31,50]. Some studies have shown that community-based methods, including personal references, local advertisements and pamphlets, indeed recruit more racially diverse samples than other methods [41], and may ensure better chances of participant retention [2,7,44,46,49].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, differences in age have be found between participants recruited via social networks * E-mail: alvaropastor@uoc.edu and other methods [17]. As well as a risk for racial and economical bias has been reported when using social networks data [19,31,50]. Moreover, the literature from a diversity of disciplines, including machine learning and data mining [6,23,36], and marketing [20,27,48], sheds light on the various management layers that aim to optimise links between users and the flow of messages.…”
Section: But How Do Social Network Work?mentioning
confidence: 99%
“…However, we were able to run automated detection software to determine the geolocation and age 33,34 of the Twitter users. In addition, two researchers (KO and SG) independently annotated basic race categories (black, Asian and white) 35 of Twitter users using their photos and self‐declarations in their bio or recent timelines.…”
Section: Methodsmentioning
confidence: 99%
“…One additional limitation to this work is the lack of disaggregation by race or gender, especially considering that a majority of ARMY are women (Grover et al 2022). While we wish to examine these topics under a lens that incorporates these demographic characteristics, such work is difficult without making generalized inferences, and there is not a uniformly accepted method for ascertaining the race or ethnicity of social media users (Golder et al 2022;Jung et al 2018). For example, many papers in computer science that examine Internet data use facial recognition or artificial intelligence (AI) software in order to derive the gender and race of respondents from Twitter profiles.…”
Section: Limitationsmentioning
confidence: 99%
“…While we wish to examine these topics under a lens that incorporates these demographic characteristics, such work is difficult without making generalized inferences, and there is not a uniformly accepted method for ascertaining the race or ethnicity of social media users (Golder et al. 2022; Jung et al. 2018).…”
Section: Limitationsmentioning
confidence: 99%